Evaluation of Polo‐like kinase 1 as a potential therapeutic target in Merkel cell carcinoma. (29th December 2015) - Kadletz, Lorenz; Bigenzahn, Johannes; Thurnher, Dietmar; Stanisz, Isabella; Erovic, Boban M.; Schneider, Sven; Schmid, Rainer; Seemann, Rudolf; Birner, Peter; Heiduschka, Gregor
Abstract: Background: Merkel cell carcinoma (MCC) is a rare and aggressive malignancy of the skin. Treatment options for MCC include surgery, radiotherapy, and chemotherapy. The purpose of this study was to assess the expression of Polo‐like kinase 1 (PLK1) in MCC and the role of the inhibitor, BI2536, as a potential therapeutic option in MCC. Methods: PLK1 expression was assessed in tissue samples from 28 patients with MCC and 5 healthy skin samples via immunohistochemistry and furthermore in the 2 MCC cell lines, MCC13 and MCC26, via immunoblotting. The impact of increasing doses of BI2536 alone and in combination with cisplatin or irradiation on cell viability was measured using the CCK‐8 assay. Colony forming assays were performed to evaluate long‐term effects of combination treatments. Additionally, the induction of apoptotic cell death was measured via flow cytometry. Results: PLK1 is moderately to strongly expressed in 75% of the patients with MCC. The PLK1 inhibitor, BI2536, demonstrated marked inhibition of cell proliferation with IC50 in the low nM range (from 10.07–12.39 nM). Furthermore, BI2536 induces apoptosis in MCC cell lines and acts synergistically in combination with irradiation and cisplatin. Conclusion: Because of the marked upregulation of PLK1 in MCC tumor samples and potent inhibition of cell proliferation using a specific clinically available inhibitor, targeting of PLK1 qualifies as a potential novel therapeutic strategy in MCC. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1918–E1925, 2016